Pneumonectomy for Treatment of Destroyed Lung: A Retrospective Study of 137 Patients - Li, Yuping; Hu, Xuefei; Jiang, Gening; Chen, Chang (The Thoracic and Cardiovascular Surgeon, 2017)
Objectives Whether pneumonectomy is needed for the treatment of destroyed lungs is still controversial and unresolved in the clinic. Pneumonectomy is destructive and is associated with a significant incidence of postoperative complications. The purpose of this study is to analyze the operative techniques, postoperative morbidity, mortality, and long-term outcomes of patients with destroyed lungs who underwent pneumonectomy.Patients and Methods We retrospectively analyzed 137 patients with destroyed lungs who underwent pneumonectomy. The data were queried for the details of operative technique, development of perioperative complications, mortality, and long-term survival. Univariate and multivariate analyses were performed to investigate the risk factors of pneumonectomy among the patients.Results A total of 77 male and 60 female patients were reviewed. The youngest patient was 18 years, and the oldest was 75 years, with a mean age of 40.1 years. Postoperative complications were observed in 25 patients (18.2%). The rate of bronchopleural fistula (BPF) was 5.1% (7/137). Two perioperative deaths (1.5%) were noted. Univariate and multivariate analyses indicated the blood loss (hazard ratio [HR], 5.32; 95% confidence interval [CI], 1.27–18.50; p = 0.021) was the independent risk factor of postoperative complications, and the type of the disease (HR, 4.50; 95% CI, 1.19–9.69; p = 0.034) was the independent risk factor of the BPF, for the patients with destroyed lung after pneumonectomy.Conclusion Pneumonectomy for destroyed lung is a high risk for postoperative complications. Our findings suggested that pneumonectomy in destroyed lung was satisfactory with strict surgical indications, adequate preoperative preparation, and careful operative technique, and the long-term outcomes can be especially satisfactory. Pneumonectomy for destroyed lung is still a treatment option.
Keywords: destroyed lung; surgery complications; outcomes; long-term survival